Analysis of the CRT Test Patterns Colours - Vaitkūnas, M.; Dosinas, A.; Bartkevičius, V. (Elektronika ir Elektrotechnika, 2005)
Investigation of some factors making influence on evaluation of the colour CRT screen test patterns parameters is presented, when colour video cameras are used for acquisition of the test patterns in automated CRT adjustment systems. One particular case was examined, when a step of CRT raster is close to a step of cameras raster, and therefore two components of cameras output signal are produced – the permanent one, that represents overall colour of the acquired picture part, and the variable component, that describes detailed structure of screen picture. The possibilities of using those components in evaluation of the test pattern parameters are analysed. The misconvergence dependence on pattern line width and size of cameras reading aperture are presented, while the geometrical structure and the colour of pattern are analysed. Ill. 3, bibl. 7 (in Lithuanian; summaries in Lithuanian, English and Russian.).